Displaced persons in South Sudan - whose responsibility to protect? - Henderson-Howat, Fenella (Department of Political Studies, 2017)
There have been severe shortcomings in the protection of internally displaced persons (IDPs), and gaps in research with academic and legal focus remaining on refugees instead. These gaps are revealed and correspondingly explored in this thesis through a case study analysis of South Sudan. The main objective of this thesis is to expose the overall protection discrepancies facing IDPs, and the need to re-address international responsibility to protect in cases where national authorities are unable or unwilling to do so. The lack of a clear definition, legal status and institutional framework at an international level is shown to have an adverse impact on protection. The case study of South Sudan is introduced through an overall analysis of key events and displacement trends. Evidence in support of the main argument is presented through an analysis of the injustices and human rights violations facing IDPs in South Sudan. The roles of the two major providers of protection in South Sudan - the national authorities and the international community - are evaluated to ultimately show how a more flexible approach must be adopted by the international community in such cases. Overall, this thesis seeks to bring the displaced in South Sudan to the forefront of the debate about who is responsible for their protection.